2021
DOI: 10.1021/acsami.0c19725
|View full text |Cite
|
Sign up to set email alerts
|

Melamine Foam Derived 2H/1T MoS2 as Flexible Interlayer with Efficient Polysulfides Trapping and Fast Li+ Diffusion to Stabilize Li–S Batteries

Abstract: Lithium–sulfur (Li–S) batteries featuring high-energy densities are identified as a hopeful energy storage system but are strongly impeded by shuttle effect and sluggish redox chemistry of sulfur cathodes. Herein, annealed melamine foam loaded 2H/1T MoS2 (CF@2H/1T MoS2) is prepared as a multifunctional interlayer to inhibit the shuttle effect, improve redox kinetics, and reduce the charge–discharge polarization of Li–S batteries. The CF@2H/1T MoS2 becomes fragmented structures after assembling the cell, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 60 publications
1
18
0
Order By: Relevance
“…With the rapidly increasing demands for electric devices, commercial lithium-ion batteries (LIBs) almost reached its limitation on accounts of its low theoretical capacity and energy density. In recent years, lithium–sulfur (Li–S) batteries are regarded as one of the most prospective new generation energy storage equipment, because of its noticeable merits, for example, desirable theoretical capacity (1675 mAh g –1 ) and energy density (2600 Wh kg –1 ), cost-effectiveness, and environmentally friendliness. However, the application of Li–S cells is faced with many technical bottlenecks, including poor electrical conductivity of sulfur and discharge end product of lithium sulfide (Li 2 S), huge volume expansion (80%) during cycling, and severe shuttling behavior derived from the dissolution of lithium polysulfides (LiPSs). The above-mentioned technical obstacles inevitably result in low sulfur utilization, sluggish reaction kinetics, rapid capacity decay, and serious anode corrosion of Li–S cells.…”
mentioning
confidence: 99%
“…With the rapidly increasing demands for electric devices, commercial lithium-ion batteries (LIBs) almost reached its limitation on accounts of its low theoretical capacity and energy density. In recent years, lithium–sulfur (Li–S) batteries are regarded as one of the most prospective new generation energy storage equipment, because of its noticeable merits, for example, desirable theoretical capacity (1675 mAh g –1 ) and energy density (2600 Wh kg –1 ), cost-effectiveness, and environmentally friendliness. However, the application of Li–S cells is faced with many technical bottlenecks, including poor electrical conductivity of sulfur and discharge end product of lithium sulfide (Li 2 S), huge volume expansion (80%) during cycling, and severe shuttling behavior derived from the dissolution of lithium polysulfides (LiPSs). The above-mentioned technical obstacles inevitably result in low sulfur utilization, sluggish reaction kinetics, rapid capacity decay, and serious anode corrosion of Li–S cells.…”
mentioning
confidence: 99%
“…1 However, large capacity decay is a common phenomenon for batteries under 0 C. Commercialized batteries can only hold about 20% of the room temperature capacity at À20 C. 2,3 Thus, it is crucial to research and develop low-temperature batteries with high capacity for practical applications. Lithium-sulfur (Li-S) batteries have been actively explored due to their high theoretical capacity (1675 mA h g À1 ) and the natural abundance of S. [4][5][6][7][8][9][10][11][12][13] The poor conductivity of S 8 and Li 2 S, the large volume expansion (80%) during cycling, and the shuttle effect caused by the dissolution of lithium poly-suldes (LiPSs) lead to the low utilization rate of active substances and rapid capacity decay, which limit its high-power output. [14][15][16][17] In addition, the heterogeneous redox reaction during the process of charge/discharge is usually accompanied by slow reaction kinetics, which causes the unsatisfactory rate capability of Li-S batteries.…”
Section: Introductionmentioning
confidence: 99%
“…While traditional electrocatalysts such as platinum-based materials remarkably improve the Li–S performance, their high cost and scarce resources persuade researchers to explore alternative catalysts for energy applications. In this context, transition metal dichalcogenides (TMDs) have attracted much interest to accelerate the Li–S reaction kinetics and their overall performance. , Through systematic electrochemical evaluation, several researchers have demonstrated the importance of such electrocatalyst nanoparticles on LiPS multistep conversion reactions. , It has been previously demonstrated that highly catalytic edge planes can effectively adsorb LiPS and favor the deposition and oxidation of the discharge end products. , It is well agreed upon that the exceptional catalytic activity of TMDs arises from the versatile and tunable electronic structure of transition metal d-orbitals and undercoordinated surface atoms, the so-called edge planes. , On one hand, several strategies have been explored to enhance the number of edge planes in TMDs to improve their activity. However, given that the inherently inert basal plane is considerably more stable and highly exposed compared to the edge planes, it would be rational to activate it to further enhance both the overall number of active sites and electrocatalytic properties.…”
Section: Introductionmentioning
confidence: 99%
“…10,12−14 multistep conversion reactions. 15,16 It has been previously demonstrated that highly catalytic edge planes can effectively adsorb LiPS and favor the deposition and oxidation of the discharge end products. 11,17−19 It is well agreed upon that the exceptional catalytic activity of TMDs arises from the versatile and tunable electronic structure of transition metal d-orbitals and undercoordinated surface atoms, the so-called edge planes.…”
Section: Introductionmentioning
confidence: 99%